PRIMARY IDENTIFICATION OF EUCALYPTUS (Eucalyptus camaldulensis) WOOD LIGNIN MONOMERS BY FT-IR SPECTROSCOPY - Esam Mohammed Sheet (Mesopotamia Journal of Agriculture)
Lignin samples were isolated from Eucalypt wood (Eucalyptus camaldulensis) by kraft process, and then all samples were examined and tested with Fourier Transform Infrared Instrument Technique for identifying the types of lignin monomers units from their spectra.The Lignin monomers spectra chart showed these peak bands( 616.80, 795.11, 876.96, 1057.14, 1127.19, 1458.74, 1509.21, 1542.05 , 1636.26, 1735.68, 2863.72,2922.35, 2967.95, 3447.01,and 3650.56 cm-1 ).No evidence for methoxyl group bands were observed, though all monomers of the tested lignin in this investigation which obtained from Eucalypt wood by KRAFT process consist mainly of P-hydroxy phenyl propane units.